2019
DOI: 10.1108/ecam-01-2019-0028
|View full text |Cite
|
Sign up to set email alerts
|

Assessing building information modeling implementation readiness in building projects in Singapore

Abstract: Purpose The purpose of this paper is to identify critical non-value adding (NVA) building information modeling (BIM) implementation activities in current building project delivery process, develop a BIM implementation readiness (BIMIR) evaluation model, and assess BIMIR statuses in building projects in Singapore. Design/methodology/approach A questionnaire survey and four post-survey interviews were conducted in Singapore. A fuzzy synthetic evaluation approach was adopted in the model development. Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…In Asia, Singapore shows great ambition in advancing mandatory use of BIM implementation. It pioneered the mandatory use of BIM in the building sector in 2012 and extended the mandate each year until 2015, making Singapore a typical successful country that adopts a government-driven approach to promoting BIM implementation (Yang and Chou, 2018; Liao et al , 2020). The Development Bureau in Hong Kong have also required BIM on capital work projects worth more than HK$30m since January 2018.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Asia, Singapore shows great ambition in advancing mandatory use of BIM implementation. It pioneered the mandatory use of BIM in the building sector in 2012 and extended the mandate each year until 2015, making Singapore a typical successful country that adopts a government-driven approach to promoting BIM implementation (Yang and Chou, 2018; Liao et al , 2020). The Development Bureau in Hong Kong have also required BIM on capital work projects worth more than HK$30m since January 2018.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhao et al [18] assessed potential risks in BIM adoption in Singapore at the firm level and did not evaluate the project-level risks. Liao et al [6] assessed BIM implementation readiness in building projects in Singapore without identifying barriers to BIM diffusion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Industry players initiate BIM adoption, prompting the government to make corresponding policies. In contrast with the US's bottom-up approach, a top-down approach is adopted in countries such as the United Kingdom and Singapore, where the governments are dominant forces in diffusing BIM adoption [5,6]. Cheng and Lu [7] observed that Singapore has issued the most (12 out of 35) BIM standards in Asia, and by far has been the only country that has mandated all new building projects (both public and private) with a gross floor area (GFA) of 5000 m 2 and above to submit building plans in BIM format since July 2015.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, at the macro level, actual circumstances of BIM promotion policies, standards, and guidelines vary from one country or city to another. Some countries such as the United Kingdom and Singapore promote BIM using a top-down approach, whereas others tend to adopt a bottom-up approach [3,4]. An increasing number of governments encourage, specify, or mandate BIM adoption, especially in publicly funded building and construction projects [5], while others opt to adopt a wait-and-see attitude [3] or even see BIM adoption as an extra effort [6].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of governments encourage, specify, or mandate BIM adoption, especially in publicly funded building and construction projects [5], while others opt to adopt a wait-and-see attitude [3] or even see BIM adoption as an extra effort [6]. Organizational readiness and practices and project characteristics may also be totally different in different projects [4]. Furthermore, project management practices in the context of COVID-19 vary in different countries.…”
Section: Introductionmentioning
confidence: 99%